Mapping of the FGF14:Nav1.6 complex interface reveals FLPK as a functionally active peptide modulating excitability. Issue 14 (15th July 2020) - Singh, Aditya K.; Wadsworth, Paul A.; Tapia, Cynthia M.; Aceto, Giuseppe; Ali, Syed R.; Chen, Haiying; D'Ascenzo, Marcello; Zhou, Jia; Laezza, Fernanda
Abstract: The voltage‐gated sodium (Nav) channel complex is comprised of pore‐forming α subunits (Nav1.1–1.9) and accessory regulatory proteins such as the intracellular fibroblast growth factor 14 (FGF14). The cytosolic Nav1.6 C‐terminal tail binds directly to FGF14 and this interaction modifies Nav1.6‐mediated currents with effects on intrinsic excitability in the brain. Previous studies have identified the FGF14 V160 residue within the FGF14 core domain as a hotspot for the FGF14:Nav1.6 complex formation. Here, we used three short amino acid peptides around FGF14 V160 to probe for the FGF14 interaction with the Nav1.6 C‐terminal tail and to evaluate the activity of the peptide on Nav1.6‐mediated currents. In silico docking predicts FLPK to bind to FGF14 V160 with the expectation of interfering with the FGF14:Nav1.6 complex formation, a phenotype that was confirmed by the split‐luciferase assay (LCA) and surface plasmon resonance (SPR), respectively. Whole‐cell patch‐clamp electrophysiology studies demonstrate that FLPK is able to prevent previously reported FGF14‐dependent phenotypes of Nav1.6 currents, but that its activity requires the FGF14 N‐terminal tail, a domain that has been shown to contribute to Nav1.6 inactivation independently from the FGF14 core domain. In medium spiny neurons in the nucleus accumbens, where both FGF14 and Nav1.6 are abundantly expressed, FLPK significantly increased firing frequency by a mechanism consistent with the ability of the tetrapeptide to interfere with Nav1.6 inactivation and potentiate persistent Na + currents. Taken together, these results indicate that FLPK might serve as a probe for characterizing molecular determinants of neuronal excitability and a peptide scaffold to develop allosteric modulators of Nav channels. Abstract : FLPK binds to the V160 residue in the FGF14 core domain at the protein:protein interaction interface of the FGF14:Nav1.6 complex. FLPK interferes with FGF14:Nav1.6 complex formation and prevents FGF14‐dependent modulation of Nav1.6 currents. FLPK binds to the FGF14 core domain, but its functional activity requires the FGF14 N‐terminal tail, a molecular determinant of Nav1.6 inactivation. In medium spiny neurons, FLPK significantly increases firing frequency suggesting the ability of the tetrapeptide to modulate Nav1.6 availability during repetitive firing.